Phosphatidylinositol kinase activity in virus-transformed and nontransformed cells. - Sugano, S (1985)
We assayed phosphatidylinositol (PI) kinase (EC 2.7.1.67) activity in detergent extracts of nontransformed or virus-transformed cells. Nontransformed chicken embryo fibroblasts (CEF) contain PI kinase activity with an apparent specific activity of 20 pmol/min per mg of protein. This activity sedimented as a single peak with a molecular weight of approximately 60,000 in a glycerol gradient, although immunoprecipitation with anti-p60src sera showed that the PI kinase activity is distinct from p60c-src. Extracts from CEF transformed by Rous sarcoma virus, Fujinami sarcoma virus, or avian sarcoma virus UR2 showed no elevation of PI kinase activity over nontransformed CEF. Removal of the oncogene products from extracts by immunoprecipitation did not change the level of PI kinase activity in extracts, suggesting that putative virus-coded PI kinases do not make a significant contribution to overall levels of PI kinase activity in transformed cells. Additionally, P140gag-fps was separated from cellular PI kinase by phosphocellulose chromatography. This partially purified fraction contained low PI kinase activity distinct from P140gag-fps, indicating that P140gag-fps has no detectable PI kinase activity.